Pengelolaan Dan Penghimpunan Dana Zakat Melalui Regulasi Daerah Pada Badan Amil Zakat (BAZNAS) Provinsi NTB, Kab. Cianjur, Padang Panjang, Sukabumi Dan Musi Banyuasin - Meichio Chio Lesmana; Mohammad Ghazali; Soritua Soritua; Yothanurma Yothanurma (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Meto, 2022)
Zakat is worship that can provide significant benefits in social life. Zakat also has a goal to fight poverty, unemployment and injustice. BAZNAS takes an important role as a non-structural government institution in carrying out its duties to collect and manage zakat funds. This study uses a qualitative method with focus group discussion (FGD) techniques with five regional BAZNAS. The results of the study indicate that the policies and regulations of the government are very influential in increasing the percentage of zakat funds collection. This is a form of synergizing with each other in collecting and managing zakat funds. Regional BAZNAS has programs that will help 8 ashnaf in the area and the role of the government as a policy maker will strengthen regional BAZNAS in carrying out optimal collection and management to create optimal economic growth.